Repeated losses of self-fertility shaped heterozygosity and polyploidy in yeast evolution - Nina Vittorelli; Cintia Gómez-Muñoz; Irina Andriushchenko; Louis Ollivier; Nicolas Agier; Stéphane Delmas; Yann Corbeau; Guillaume Achaz; Marco Cosentino Lagomarsino; Gianni Liti; Bertrand Llorente; Gilles Fischer (Proceedings of the National Academy of Sciences, 2026)
Evolutionary transitions in mating strategy have profound consequences for genetic variation and adaptation. In Saccharomyces cerevisiae , mating-type switching is a central feature of the life cycle that enables haploid cells to be self-fertile and mate with their own mitotic descendants (homothallism). Yet heterothallic isolates that have lost this ability are found across diverse niches, indicating that this trait is polymorphic. Here, we experimentally characterized loss of mating-type switching in a representative panel of strains. Analysis of 117 telomere-to-telomere genome assemblies revealed multiple independent loss-of-function mutations in the Ho endonuclease gene and structural variants in the silent HML and HMR cassettes, the three loci essential for switching. We estimated that at least 13 independent transitions from homothallism to heterothallism have occurred in the species history. Analysis of the HO genotype of 2,910 strains shows that at least 27% are heterothallic. We found that heterothallism is strongly associated with polyploidy and elevated genome-wide heterozygosity, although the strength of these associations varies between populations. Heterothallic isolates are most prevalent in domesticated and clinical clades, consistent with an origin linked to human-associated environments. However, they are also found, though less frequently, in natural niches. Signatures of recombination in HO sequences suggest that outcrossing contributed to the ecological and geographical distribution of the trait. Our findings reveal that mating-type switching has undergone repeated losses in S. cerevisiae evolution, with major consequences for genome architecture and ecological diversification.